A new species of the genus Trouessartia Canestrini (Acari: Trouessartiidae) from Neotropical passerines (Aves: Tyrannidae) - Hernandes, Fabio Akashi [UNESP] (2015)
A new species of the feather mite genus Trouessartia Canestrini (Acari: Trouessartiidae) is described from Myiobius atricaudus Lawrence, 1863 (Aves: Passeriformes: Tyrannidae) from Brazil. Trouessartia longiducta sp. nov. is remarkable in having the longest external copulatory tube in females among species of the genus Trouessartia. It differs from the closest species T. geospiza OConnor et al., 2005 in having the female copulatory tube extending beyond the level of lobar apices.